A Course Model for Building Evaluation Capacity Through a University–Community Partnership. (December 2014) - Bakken, Lori L.; Núñez, Jennifer; Couture, Cathy
Program evaluation is recognized as an essential skill set for practitioners in service-related fields, such as education, nonprofit management, social work, and public health. Recently, the need for a public workforce trained in evaluation has increased and is driven primarily by our nation's emphasis on accountability during a time when financial resources are limited. However, many of these professionals lack the necessary skills to conduct evaluations of their programs and often rely on a much smaller number of evaluation consultants to perform this task. How then can we educate students and professionals in ways that build evaluation capacity among service organizations and meet these growing needs? A novel course design that integrates principles of adult learning, participatory evaluation approaches, and experiential forms of learning to build evaluation capacity among students and a nonprofit organization is presented. Evidence is provided to demonstrate student learning and the impact of the course on the nonprofit service organization's evaluation capacity.